2011
DOI: 10.1021/nn1021007
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Poly(amidoamine) Dendrimers with Human Serum Albumin: Binding Constants and Mechanisms

Abstract: The interactions of nanomaterials with plasma proteins have a significant impact on their in vivo transport and fate in biological fluids. This article discusses the binding of human serum albumin (HSA) to poly(amidoamine) [PAMAM] dendrimers. We use protein-coated silica particles to measure the HSA binding constants (K b) of a homologous series of 19 PAMAM dendrimers in aqueous solutions at physiological pH (7.4) as a function of dendrimer generation, terminal group, and core chemistry. To gain insight into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
90
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 46 publications
11
90
0
1
Order By: Relevance
“…S1) as well as the mixtures of this drug and PAMAM G5-OH (Fig. S2) in heavy water as in previous 1 H NMR studies of PAMAM-NH 2 (Bányai et al, 2013;Barra et al, 2014a,b;Buczkowski et al, 2012bBuczkowski et al, , 2013Cao et al, 2013;Giri et al, 2011;Hu et al, 2010Hu et al, , 2012Keri et al, 2015) and PAMAM-OH dendrimers (Choi et al, 2012;Giri et al, 2011;Gomez et al, 2009a,b;Hu et al, 2012;Pellechia et al, 2004;Wang et al, 2013). With increasing the concentration of 5-fluorouracil in the mixture of drug and dendrimer one can observe that peak at 2.6 ppm corresponding to the protons of methylene groups present at tertiary amine groups is not clearly shifted during the drug bonding by cationic PAMAM G5-NH 2 dendrimer (Fig.…”
Section: H Nmr Spectroscopysupporting
confidence: 62%
“…S1) as well as the mixtures of this drug and PAMAM G5-OH (Fig. S2) in heavy water as in previous 1 H NMR studies of PAMAM-NH 2 (Bányai et al, 2013;Barra et al, 2014a,b;Buczkowski et al, 2012bBuczkowski et al, , 2013Cao et al, 2013;Giri et al, 2011;Hu et al, 2010Hu et al, , 2012Keri et al, 2015) and PAMAM-OH dendrimers (Choi et al, 2012;Giri et al, 2011;Gomez et al, 2009a,b;Hu et al, 2012;Pellechia et al, 2004;Wang et al, 2013). With increasing the concentration of 5-fluorouracil in the mixture of drug and dendrimer one can observe that peak at 2.6 ppm corresponding to the protons of methylene groups present at tertiary amine groups is not clearly shifted during the drug bonding by cationic PAMAM G5-NH 2 dendrimer (Fig.…”
Section: H Nmr Spectroscopysupporting
confidence: 62%
“…29 In the case of dendrimers, previous studies have demonstrated that a few molecules of dendrimers and one molecule of albumin form an assembly, which is sustained for a long period of time. 30,31 These reports partially lend support to the results of our initial FCS, which indicated that cationic dendrimers and HSA formed 1:1 assemblies in PBS (-). Our further FCS analysis, however, revealed that mixing of HSA in PBS (+) led to the formation of dendrimer aggregates of submicron-or larger sizes.…”
supporting
confidence: 71%
“…4c) differentiate these samples from typical DOM. Closer inspection reveals that many of these largest peaks are consistent with protein resonances 23,24 .…”
Section: Resultsmentioning
confidence: 88%